Supplement intake in half-marathon, (ultra-)marathon and 10-km runners – results from the NURMI study (Step 2). Issue 1 (27th September 2021) - Katharina, Wirnitzer; Mohamad, Motevalli; Derrick, Tanous; Martina, Gregori; Gerold, Wirnitzer; Claus, Leitzmann; Lee, Hill; Thomas, Rosemann; Beat, Knechtle
Abstract: The primary nutritional challenge facing endurance runners is meeting the nutrient requirements necessary to optimize the performance and recovery of prolonged training sessions. Supplement intake is a commonly used strategy by elite and recreational distance runners to meet nutritional recommendations. This study was conducted to investigate the patterns of supplement intake among different groups of distance runners and the potential association between supplement intake and sex, age, running and racing experiences. In a cross-sectional design, from a total of 317 runners participating in this survey, 119 distance runners were involved in the final sample after data clearance, assigned into three groups of 10-km runners (n = 24), half-marathoners ( n  = 44), and (ultra-)marathoners (n = 51). Personal characteristics, training and racing experiences, as well as patterns of supplement intake, including type, frequency, and dosage, were evaluated by questionnaire. Food Frequency Questionnaire was implemented to assess macronutrient intake. ANOVA and logistic regression were used for statistical analysis. While 50 % of total distance runners reported consuming supplements regularly, no differences between distance groups in consumption of carbohydrate/protein, mineral, or vitamin supplements were observed (p > 0.05). In addition, age, sex, running and racing experience showed no significant association with supplement intake ( p  > 0.05). Vitamin supplements had the highest intake rate in runners by 43 % compared to minerals (34 %) and carbohydrate/protein supplements (19 %). The present findings provide a window into the targeted approaches of long-distance runners as well as their coaches and sport nutrition specialists when applying and suggesting sustainable nutritional strategies for training and competition. Trial registration : ISRCTN73074080. Retrospectively registered 12th June 2015.